A Power Case Study for Monocrystalline and Polycrystalline Solar Panels in Bursa City, Turkey - Ayşegül Taşçıoğlu; Onur Taşkın; Ali Vardar (International Journal of Photoenergy)
It was intended to reveal the time dependent power generation under different loads for two different solar panels under the conditions of Bursa province in between August 19 and 25, 2014. The testing sets include solar panels, inverter, multimeter, accumulator, regulator, pyranometer, pyrheliometer, temperature sensor, and datalogger. The efficiency of monocrystalline and polycrystalline solar panels was calculated depending on the climatic data’s measurements. As the result of the study, the average performances of monocrystalline and polycrystalline panels are 42.06 and 39.80 Wh, respectively. It was seen that 87.14 W instantaneous power could be obtained from monocrystalline solar panel and that 80.17 W instantaneous power could be obtained from polycrystalline solar panel under maximum total radiation (1001.13 W/m2). Within this frame, it was determined that monocrystalline solar panel is able to operate more efficiently under the conditions of Bursa compared to polycrystalline solar panel. When the multivariate correlations coefficients were examined statistically, a significant relationship in positive direction was detected between total and direct radiation and ambient temperature on energy generation from monocrystalline and polycrystalline panel.